2013
DOI: 10.1002/lary.24295
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of subcutaneous immunotherapy for allergic rhinoconjunctivitis and asthma: A Systematic Review

Abstract: Generally moderate to strong evidence supports the effectiveness of SCIT for treatment of allergic rhinitis and asthma, particularly with single-allergen immunotherapy regimens. Adverse reactions to SCIT are common, but no deaths were reported in the included studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 72 publications
(437 reference statements)
4
89
0
7
Order By: Relevance
“…Allergen-specific immunotherapy (AIT) using standardized vaccines is an effective treatment for allergic rhinitis and allergic asthma and is the only treatment addressing the underlying cause of allergic diseases [1,2]. AIT has the potential to modify the development of disease and has a long-term prevention effect on asthma [3].…”
Section: Introductionmentioning
confidence: 99%
“…Allergen-specific immunotherapy (AIT) using standardized vaccines is an effective treatment for allergic rhinitis and allergic asthma and is the only treatment addressing the underlying cause of allergic diseases [1,2]. AIT has the potential to modify the development of disease and has a long-term prevention effect on asthma [3].…”
Section: Introductionmentioning
confidence: 99%
“…This treatment also significantly reduced allergen-induced bronchoconstriction; however, only 20 studies included pulmonary function measurements. A few years later, Erekosima et al [82] carried out a systematic review of randomized controlled trials on the effectiveness and safety of SCIT for allergic rhinoconjunctivitis and asthma. They concluded that there was high-grade evidence that SCIT reduces asthma symptoms and asthma medication in comparison to placebo or usual care.…”
Section: Subcutaneous Immunotherapymentioning
confidence: 99%
“…-SCIT reduces asthma symptoms and asthma medication in comparison to placebo or usual care (LE 1a, grade A) [82]. -SCIT mite-sensitized subjects requires long-term treatment to achieve its clinical benefits (LE 1b, grade A) [83][84][85][86] [92,94].…”
Section: Sublingual Immunotherapymentioning
confidence: 99%
“…The preventive benefits of AIT may be greater if initiated early in the course of the allergic disease [21,22]. AIT administered subcutaneously (subcutaneous immunotherapy [SCIT]) has demonstrated efficacy at reducing the symptoms of AR caused by plant pollens, and the use of symptomatic pharmacotherapy in patients with AR and ARC [23,24]. However, the necessity for multiple injections over a period of years, and the possibility of serious systemic side effects or life-threatening anaphylaxis, especially in patients with comorbid asthma [25], has prompted the development of alternative routes of administration.…”
mentioning
confidence: 99%